Penjadwalan Predictive Maintenance dan Biaya Perawatan Mesin Pellet di PT Charoen Pokphand Indonesia - Sepanjang - Soesetyo, Ivan; Bendatu, Liem Yenny (Jurnal Titra, 2014)
In this thesis we elaborated the predictive maintenance for the critical parts of Pelletizer machines in PT. Charoen Pokphand Indonesia. We used the reliability tools, such as, availability, mean time to failure and mean time to repair for calculating the total minimum cost. As the result we can improve the availability of pelletizer 1, 3 and 4 as much as 1%, 1% and 3 % respectively. Additionally, the reliability of pelletizer 1 and 2 are improved to 20.55%, 19.71% respectively and the total cost is reduced from 12% to 90%.